Efficacy of Aeromonas hydrophila formalin-killed cells and lipopolysaccharides vaccines in maternal immunity of tilapia broodstock and the offspring resistance - Mulyani, Rahma; Sukenda, Sukenda; Nuryati, Sri (Jurnal Akuakultur Indonesia, 2019)
ABSTRACT The study aimed to analyze the efficacy of Aeromonas hydrophila formalin-killed cells (FKC) and lipopolysaccharides (LPS) vaccines in maternal immunity of tilapia broodstock and the resistance of the offsprings. This study consisted of two consecutive studies. Firstly, the broodstocks were vaccinated with PBS (non-vaccinated), FKC, LPS, and combinations of  FKC and LPS. Secondly, the offsprings from both the vaccinated and non‒vaccinated broodstock were vaccinated with the same vaccine for broodstock by immersion method. After vaccination, the offsprings were challenged with pathogenic A. hydrophila. Antibody level and lysozyme were measured in the broodstock, egg, and offsprings. In the first experiment, the result showed that vaccinated broodstock and their offsprings had delivered a significant antibody level and lysozyme activity compared with the control.  The highest relative percent survival (RPS) of offspring resulted from the combination of  FKC and LPS vaccinated broodstock at 5, 10, and 15 days post-hatching at 85.00%, 75.23%, and 67.56%, respectively.  The second experiment showed vaccinated offsprings produced from vaccinated broodstock had a higher RPS than the RPS of vaccinated offsprings which produced from non-vaccinated broodstock. In conclusion, vaccination that using a combination of FKC and LPS vaccine in broodstock potentially improved the maternal immunity and protect their offspring from A. hydrophila infection. Keywords: Aeromonas hydrophila, antibody, maternal immunity, tilapia, vaccination ABSTRAK Penelitian ini bertujuan menganalisis efikasi vaksin formalin-killed cells (FKC) dan lipopolisakarida (LPS) Aeromonas hydrophila pada imunitas maternal induk ikan nila dan ketahanan benih yang dihasilkan. Dalam penelitian ini, terdapat dua penelitian. Pertama, induk ikan nila divaksin dengan PBS (non-vaksinasi), vaksin FKC, LPS, dan kombinasi vaksin FKC dan LPS. Benih selanjutnya diuji ditantang dengan menggunakan  patogen A. hydrophila pada 5, 10, dan 15 hari pasca menetas. Kedua, benih yang dihasilkan oleh induk yang telah divaksinasi dan induk yang tidak divaksinasi tersebut divaksin dengan vaksin yang sama seperti pada induk dengan metode imersi. Setelah vaksinasi, keturunan diuji tantang dengan patogen A. hydrophila. Tingkat antibodi dan lisozim diukur pada induk, telur, dan benih. Pada percobaan pertama, hasilnya menunjukkan bahwa induk yang divaksinasi dan benih menunjukkan tingkat antibodi dan aktivitas lisozim yang signifikan dibandingkan dengan kontrol. Persentase kelangsungan hidup relatif (RPS) tertinggi benih yang dihasilkan dari induk yang divaksinasi FKC dan LPS masing-masing pada 5,10, dan 15 hari pascatetas pada 85,00%; 75,23%; dan 67,56%. Percobaan kedua menunjukkan bahwa benih yang divaksinasi dari induk yang divaksin menunjukkan RPS yang lebih baik daripada benih yang divaksinasi dari induk yang tidak divaksin. Vaksinasi menggunakan kombinasi FKC dan LPS pada induk berpotensi meningkatkan kekebalan induk dan melindungi benih dari infeksi A. hydrophila. Kata kunci: Aeromonas hydrophila, antibodi, imunitas induk, nila, vaksinasi